# Let f be the function given by f(x) = 3e^{2x} and let g be the function given by g(x) = 6x^{3}. Find (f × g)(x).

We will use the concept of functions in order to find the required function.

## Answer: (f × g) (x) = (f × g) (x) = 18 e^{2x} x^{3}, if the function given by f(x) = 3e^{2x} and let g be the function given by g(x) = 6x^{3}.

Let us see how we will use the concept of functions

**Explanation:**

We know that

(f + g) (x) = f(x) + g(x)

(f - g) (x) = f(x) - g(x)

(f × g) (x) = f(x) × g(x)

(f / g) (x) = f(x) / g(x)

Now, we have to calculate (f × g)(x).

Hence, using the above concept,

(f × g) (x) = f(x) × g(x)

(f × g) (x) = 3e^{2x} × 6x^{3}